The Readiness of Automotive Manufacturing Company on Industrial 4.0 Towards Quality Performance - Tasmin, Rosmaini; Rahman, Nurul Syahira; Jaafar, Ishaq; Abd Hamid, Nor Aziati; Ngadiman, Yunos (International Journal of Integrated Engineering, 2020)
This research is focusing on analyzing readiness of automotive manufacturing firm on Industry 4.0 towards quality performance. In the era of globalization, most manufacturing firms all over the world are constantly looking for ways to increase productivity. The manufacturing industry is mainly faced with the problem of Industry 4.0’s awareness and implementation. Top and middle management of DRB-HICOM Automotive manufacturing firm from all departments have been selected as a sample study. The questionnaire has been used to get the feedback from top and middle management about readiness of Industry 4.0. There are three main objectives that were assessing the level of firm’s characteristics, determining the level of Industry 4.0 readiness for DRB-HICOM Automotive manufacturing company, namely via variables of Applied Technology, Enterprise Resource Planning (ERP), Internet of Things (IoT), Cyber Physical System (CPS) and determining the relationship between the Industry 4.0 and quality performance. Quantitative method was used in this research which incoperates the distribution of 96 questionnaires to the respondents involving DRB-HICOM Automotive manufacturing firm. In terms of conducting the required data analysis, Statistical Package for Social Science (SPSS) version 22 was used. Result shows that all related constructs have a significant yet strong relationship between Industry 4.0 and quality performance. It is hoped that this initial Industry 4.0 work will help to spur future research about implementation of Industry 4.0, across the boards among many industrial sectors.